2019
DOI: 10.1109/access.2018.2889219
|View full text |Cite
|
Sign up to set email alerts
|

OFDM Modulated PNC in V2X Communications: An ICI-Aware Approach Against CFOs and Time-Frequency-Selective Channels

Abstract: This paper studies the application of physical-layer network coding (PNC) in vehicleto-everything communications to accommodate the time-critical nature of vehicular ad-hoc networks (VANETs). The idea can theoretically reduce the transmission latency by 50%, thus alleviating the short contact time issues caused by high-speed vehicle motion. Conventional studies of PNC primarily considered static networks. In highly mobile networks like VANETs, the carrier frequency offsets (CFOs) due to high-speed motion will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…where 𝑈 𝑡𝑜𝑡 is the resultant electric-field envelope, 𝑅 𝑎 is the reflection coefficient of the 𝑎-th path, 𝐷 𝑒 is the diffraction coefficient of the 𝑒-th path, and 𝑃 𝑟 is the received power. We implement the network simulation accordingly, the location is the intersection of Fong Shu Chuen Hall on PolyU campus, which the simulation result is consistent with the empirically collected dataset in our previous work [22]. As shown in Fig.…”
Section: B City-model-aware Channel Modelingsupporting
confidence: 75%
See 1 more Smart Citation
“…where 𝑈 𝑡𝑜𝑡 is the resultant electric-field envelope, 𝑅 𝑎 is the reflection coefficient of the 𝑎-th path, 𝐷 𝑒 is the diffraction coefficient of the 𝑒-th path, and 𝑃 𝑟 is the received power. We implement the network simulation accordingly, the location is the intersection of Fong Shu Chuen Hall on PolyU campus, which the simulation result is consistent with the empirically collected dataset in our previous work [22]. As shown in Fig.…”
Section: B City-model-aware Channel Modelingsupporting
confidence: 75%
“…As shown in Fig. 3(b), on-road V2I experiments based on universal software radio peripheral (USRP) were conducted on PolyU campus to collect experimental vehicular channel data [22]. One set of the data is used in the training dataset for the CMA channel modeling approach, and another set is used as testing data to verify the performance of the proposed models.…”
Section: B City-model-aware Channel Modelingmentioning
confidence: 99%
“…Meanwhile, protected data exchange and vehicle identity privacy are used to overcome security problems by using the ElGamal encryption technique with a tweaked Schnorr signature technique. In addition, incorporating physical layer network (PNC) coding in vehicle-to-all communications to handle time-critical properties will minimize short touch time issues created by high-speed vehicle travel [41]. General conceptualizations that can be extended to the communication domain of an Intelligent Transportation System (ITS) enable the exchanging of information between applications and services running on the equipment that makes up a VANET, particularly moving vehicles, fixed road infrastructure systems, and mobile personal devices [42].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, JD provides better performance than SIC at the cost of higher complexity. Network-Coded Multiple Access (NCMA) is an example of JD-based NOMA scheme that employs Physical-layer Network Coding (PNC) to boost the throughput [8] [9]. Focusing on message exchange among multiple vehicles, our previous work showed that NCMA provided higher throughput performance as compared with SIC and the complexity can be reduced by exploiting the side information [10][11].…”
Section: Introductionmentioning
confidence: 99%